2022
DOI: 10.1002/aoc.6922
|View full text |Cite
|
Sign up to set email alerts
|

New gold(III) chlorophenyl terpyridine complex: Biomolecular interactions and anticancer activity against human oral squamous cell carcinoma

Abstract: In this work we synthesized new monofunctional gold(III) complex [Au(Cl‐Ph‐tpy)Cl]Cl2 (Cl‐Ph‐tpy = 4′‐[4‐chlorophenyl]‐2,2′:6′, 2″‐terpyridine). This complex was characterized by UV–Vis, NMR, IR, and ESI‐MS spectrometry. The kinetic study of the substitution reactions of the Au‐Cl‐Ph‐tpy complex with biomolecules showed that the rate constants depend on the nature of the entering nucleophile. Based on the calculated values of entropy (∆H≠ > 0) and enthalpy (∆S≠ < 0) the proposed substitution mechanism is assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 111 publications
0
5
0
Order By: Relevance
“…The band at 265 nm corresponds to the intra-ligand (π → π*) charge transfer, while the bands at 300/305 nm and 310/315 nm are described as ligand-to-metal charge transfer (LMCT). [23] While the dinuclear gold(III) complex is neutral, the dissociation of one chloride ligand results in the corresponding molecular ion [C 8 H 6 Au 2 Cl 5 N 2 ] + (m/z 700.8246), which could be detected by Cryospray-MS analysis. Its recorded isotope pattern also ts the simulation, supporting this assignation (ESI, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The band at 265 nm corresponds to the intra-ligand (π → π*) charge transfer, while the bands at 300/305 nm and 310/315 nm are described as ligand-to-metal charge transfer (LMCT). [23] While the dinuclear gold(III) complex is neutral, the dissociation of one chloride ligand results in the corresponding molecular ion [C 8 H 6 Au 2 Cl 5 N 2 ] + (m/z 700.8246), which could be detected by Cryospray-MS analysis. Its recorded isotope pattern also ts the simulation, supporting this assignation (ESI, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the decrease in uorescence intensity is caused by the displacement of EB from EB-DNA system. [23] The uorescence titration of EB-DNA with the increasing concentration of dinuclear gold(III) complex (1.35-13.9 µM) is shown in Fig. 2.…”
Section: Competitive Uorescence Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies carried out with this complex revealed a decreasing reactivity trend among selected nucleophiles, with 5′‐GMP exhibiting the highest reactivity, followed by L–Met and GSH, implying that the guanine derivative is a more effective entering nucleophile than the studied S‐donor ligands. The complex displayed moderate binding affinities for both CT DNA and BSA, whereas molecular docking confirmed intercalation as the primary binding mode with DNA and identified the binding pocket at site I of BSA [42] …”
Section: Terpyridine‐based Gold Complexesmentioning
confidence: 97%
“…The complex displayed moderate binding affinities for both CT DNA and BSA, whereas molecular docking confirmed intercalation as the primary binding mode with DNA and identified the binding pocket at site I of BSA. [42] A distinct family of terpyridine-gold(III) complexes (Au5a-Au5c), featuring various 4'-phenyl substituents, exhibited remarkable cytotoxicity, surpassing cisplatin in multiple cancer cell lines. Notably, the corresponding ligands also demonstrated significant cytotoxicity against the tested cell lines.…”
Section: Terpyridine-based Gold Complexesmentioning
confidence: 99%